Thermodynamics and kinetics of protein incorporation into membranes. - Jähnig, F (Proc Natl Acad Sci U S A, 1983)
The free energy and enthalpy of protein incorporation into membranes are calculated with special emphasis on the hitherto neglected effects of immobilization of protein and perturbation of lipid order in the membrane. The free energy change is found to be determined by the hydrophobic effect as the driving force for incorporation and the protein immobilization effect which leads to a considerable reduction of the free energy gained from the hydrophobic effect. For incorporation of a hydrophobic, bilayer-spanning alpha-helix, the free energy change obtained is of the order of -15 kcal/mol (1 cal = 4.184 J) in agreement with experimental results. The lipid perturbation effect yields only a small contribution to the free energy change due to an energy/entropy compensation inherent in lipid order. This effect dominates the enthalpy change, giving rise to values on the order of 100 kcal/mol with a pronounced temperature dependence around the lipid phase transition as observed experimentally. The kinetics of protein incorporation are even more strongly affected by the lipid perturbation effect, leading to an abrupt decrease of the rate of incorporation below the lipid phase transition.